Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Pelanggan Percetaakan Dwi Jaya Mulya - Rizqulloh, Achmad Afif (PRAGMATIS, 2025)
Dwi Jaya Printing is experiencing problems with fluctuations in the number of customers per quarter from 2023 to 2024 which is caused by customer dissatisfaction. Public complaints about long queue times and the printing process still seem to be obstacles that CV cannot fully overcome. Dwi Jaya Mulia Gersik city branch. This research aims to determine the partial influence of service quality and company image on customer satisfaction at the Dwi Jaya Mulia printing press, Gresik City Branch. The research approach used is quantitative research. The population used is all CV printing customers. Dwi Jaya Mulia with a sampling technique, namely using non-probability sampling with a purposive sampling technique, so that a sample size of 105 people was obtained. Data collection was obtained from questionnaires distributed to the sample. The measurement scale used in this research is four Likert scales. The data obtained was then processed using multiple linear regression analysis using SPSS ver 24 software. The research results concluded that service quality influences customer satisfaction at Dwi Jaya Mulia printing. Likewise, company image has an influence on customer satisfaction at Dwi Jaya Mulia printing. The managerial implication that can be given to Dwi Jaya Mulia printing is to always accept criticism and suggestions well which can be used as motivation to improve performance.